If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 4) = 3(6x + -5) Reorder the terms: 2(4 + 3x) = 3(6x + -5) (4 * 2 + 3x * 2) = 3(6x + -5) (8 + 6x) = 3(6x + -5) Reorder the terms: 8 + 6x = 3(-5 + 6x) 8 + 6x = (-5 * 3 + 6x * 3) 8 + 6x = (-15 + 18x) Solving 8 + 6x = -15 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 8 + 6x + -18x = -15 + 18x + -18x Combine like terms: 6x + -18x = -12x 8 + -12x = -15 + 18x + -18x Combine like terms: 18x + -18x = 0 8 + -12x = -15 + 0 8 + -12x = -15 Add '-8' to each side of the equation. 8 + -8 + -12x = -15 + -8 Combine like terms: 8 + -8 = 0 0 + -12x = -15 + -8 -12x = -15 + -8 Combine like terms: -15 + -8 = -23 -12x = -23 Divide each side by '-12'. x = 1.916666667 Simplifying x = 1.916666667
| 9+7j=4j | | X+5-2x=3+x | | x=2000000+0.333y | | 2x-24=82 | | -7-3n=-5n | | -7-2r=4+9r | | 2+4*5=30 | | -8=-3n+5n | | -6(-m-8)=-10m | | (2x-1)/3=(5x-6)/4 | | -10-7q=10-9q | | 11n-9=5n+45 | | 3(2r+14)=2(25+4) | | -9-9(13t-1)=6(-20t-10) | | 5n+22=22 | | 3(f-2)=7(f+2) | | C+5-2x=3+x | | -4y+b= | | 4(x+5)=-4x-20 | | 12n+22=5 | | 18d+18+20=2(15d-17) | | 5(x+1)-6x=-11x | | f(p)=p^2-6p+1 | | y=3500x+31500 | | y-14=y | | 2.8v-3.54-17.4v=-9.19-15.1v | | 12n+22=44 | | (x-3/2)^2-5/4=0 | | 10-5s=-10-3s | | (2x-7)/5=4⋅(x-2) | | 5(2k+3)-8=6p+29 | | 12n+22=128 |